Game Edukasi Mata Pelajaran Matematika Kelas VI Sekolah Dasar Berbasis Android - Indaryanti, I; Suppa, Rinto; Apriyanto, A (STIKOM Tunas Bangsa Pematangsiantar, 2021)
This study aims to describe the development of learning media for Android-based elementary school mathematics educational games for mathematics lessons in elementary schools. From the results of this study, the research method chosen is the waterfaal method, with a development model consisting of 5 stages, namely: (1) planning stage, (2) design stage, (3) manufacture stage, (4) testing stage, (5 ) Implementation Phase. The results of the determination show that the Android-based educational game teaching facility for elementary school mathematics is feasible to use for learning elementary school mathematics. The design of this application is specifically for students as users. The application is designed for a running system that will be built in the form of a Use Case.